Matech engineering enterprise / Muhammad Faiz Ramli...[et al.] - Ramli, Muhammad Faiz; Roselan, Muhammad Syamim; Musa, Noorazian; Md Yassin, Nurafifah; Mohktar, Nurul Atikah (2015)
Matech Engineering Enterprise is a locally owned and a rare facilities company that will be positioned as one of the top engineering company through our creative approach to the company's image. Matech Engineering Enterprise will provide a combination of cool, attractive, creative, innovative, and invention product. Multifunction glass board is the answer to an increasing demand for creative and innovative to the universities, hospital, and big company in our country especially for learning process. Our company is locating at No 3, Jalan Sesiku 1502 Shah Alam, Industrial Site 47300 Shah Alam, Selangor Darul Ehsan. We chooses this location because we want to develop and give work opportunities to community in this area. This business is based on partnership where it consists of five members. The members consist of General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. Despite that, we have 5 workers that will work at our company. One person under marketing and four people will work under operation. Business capital is amounted RM 500 000 where general manager RM 120 000 and each of other manager are RM95 000. Each manager has their own responsibilities. General Manager will make decision in management business, carry up objective and try to achieve it and having good relationship communication with customer and staff. Administration Manager will determine the wages and salaries received by workers and contribute the percentage of the salaries to ERF and SOCSO, and to assist General Manager in business. Financial Manager is to maintain the financial of company, control the inflow and outflow of company financial. Operational Manager will make sure that the entire worker does their work and ensure all material to make product is enough. Marketing Manager do survey and research on market potential and create marketing strategies with creativity and innovative in management activities. Every business has their own competitor and for our business, the competitors we can assure are Goodwrite Sdn Bhd ,Writebest Sdn Bhd and Vision Enterprise Sdn Bhd. All of them sell almost the same product as us. However, our business has its own strength. Our strength is that our product is rarely to find on market. Our product has high technologies that will attract customers to buy this, it also provide with multi-function that can be adjusted to any angle and become glassboard and table. Other than that, we offer wheel under it feet which is easier to move and it has light weight compare to others.